Chronic exposure to KATP channel openers results in attenuated glucose sensing in hypothalamic GT1-7 neurons. (December 2016) - Haythorne, Elizabeth; Hamilton, D. Lee; Findlay, John A.; Beall, Craig; McCrimmon, Rory J.; Ashford, Michael L.J.
Abstract: Individuals with Type 1 diabetes (T1D) are often exposed to recurrent episodes of hypoglycaemia. This reduces hormonal and behavioural responses that normally counteract low glucose in order to maintain glucose homeostasis, with altered responsiveness of glucose sensing hypothalamic neurons implicated. Although the molecular mechanisms are unknown, pharmacological studies implicate hypothalamic ATP-sensitive potassium channel (KATP ) activity, with KATP openers (KCOs) amplifying, through cell hyperpolarization, the response to hypoglycaemia. Although initial findings, using acute hypothalamic KCO delivery, in rats were promising, chronic exposure to the KCO NN414 worsened the responses to subsequent hypoglycaemic challenge. To investigate this further we used GT1-7 cells to explore how NN414 affected glucose-sensing behaviour, the metabolic response of cells to hypoglycaemia and KATP activity. GT1-7 cells exposed to 3 or 24 h NN414 exhibited an attenuated hyperpolarization to subsequent hypoglycaemic challenge or NN414, which correlated with diminished KATP activity. The reduced sensitivity to hypoglycaemia was apparent 24 h after NN414 removal, even though intrinsic KATP activity recovered. The NN414-modified glucose responsiveness was not associated with adaptations in glucose uptake, metabolism or oxidation. KATP inactivation by NN414 was prevented by the concurrent presence of tolbutamide, which maintains KATP closure. Single channel recordings indicate that NN414 alters KATP intrinsic gating inducing a stable closed or inactivated state. These data indicate that exposure of hypothalamic glucose sensing cells to chronic NN414 drives a sustained conformational change to KATP, probably by binding to SUR1, that results in loss of channel sensitivity to intrinsic metabolic factors such as MgADP and small molecule agonists. Highlights: Chronic exposure to NN414 blunts hypoglycaemic responses in GT1-7 neurons. NN414 does not cause adaptations in glucose metabolism. The availability of KATP to open is greatly diminished by NN414. Preventing NN414 binding or conformation change to KATP rescues channel activity.